PROGRAM PELATIHAN TUTOR UNIVERSITAS TERBUKA - TRINI PRASTATI (Jurnal Evaluasi Pendidikan, 2011)
The goal of this evaluation research on the Open University Tutor Training Program is to measure the worth of the program whether or not the program is successful to make the tutor in Universitas Terbuka professional in doing their duties in Tutorial Tatap Muka (TTM) or face to Face Tutorial. This evaluation reserach applied the CIPP model of Stufflebeam which was combined with the 3 Dimensions Cube Model of Hammond. The study concluded that: (1) the objective of the program had been initiated based on the tutors’ needs, the instructional analysis, and the poilcies taken out by the institution, (2) the training program had been arranged so that it could reach the objectives which were made. The training program also featured procedures and strategyc training activities though the training assignment draft was still on the process to gain its perfectness based on the participants’ competencies, (3) The training program had been implemented based on the training program concept which had been decided. However, some elements in the training program still had to be optimized in order to cover all the training materials, and (4) the result of the training program was it succeeded to gain the level of the participants’ ability. The result concluded that the training program gave contribution to participants experiements in the materials given.